The Social and Economic Mission of Social Enterprises: Dimensions, Measurement, Validation, and Relation - Stevens, Robin; Moray, Nathalie; Bruneel, Johan (Entrepreneurship Theory and Practice, 2015)
Social entrepreneurs have a dominant social mission and generate revenue to ensure financial viability. However, most research treats the extent to which social entrepreneurs actually adhere to social and economic mission as a black box. Performing higher order confirmatory factor analysis on a sample of social enterprises (N∼270), this study identifies dimensions and validates measures for understanding and delineating social and economic missions, and shows how the two constructs relate to each other. The theoretical untangling and the empirical validation of social and economic missions as distinct constructs—and multiple potential constellations of attached relative importance—opens up opportunities for quantitative hypothesis–testing research in social entrepreneurship.